The experimental proof of Mott exciton-plasma phase transition - Garkavenko A. S. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2010)
The dependence has been measured for the spontaneous radiation τ average life from the excitation level (non-equilibrium charge ΔN carrirers concentration) on particularly clear optically homogeneous monocrystals. Results of the experiment confirm earlier theoretically predicted so called Mott exciton-plasma phase transition. Itўs also indicated by results for spectral research of excited crystals photolumi-nescence obtained in this work.